2018
DOI: 10.5194/hess-22-4621-2018
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the soil water retention curve from the particle size distribution based on a pore space geometry containing slit-shaped spaces

Abstract: Abstract. Traditional models employed to predict the soil water retention curve (SWRC) from the particle size distribution (PSD) always underestimate the water content in the dry range of the SWRC. Using the measured physical parameters of 48 soil samples from the UNSODA unsaturated soil hydraulic property database, these errors were proven to originate from an inaccurate estimation of the pore size distribution. A method was therefore proposed to improve the estimation of the water content at high suction hea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Therefore, for the similar textures, the γ $\gamma $ can be assumed constant. According to the sand fraction of the samples, Chang and Cheng (2018) provided a reference for determining the γ $\gamma $ values, which could be served as input parameters to predict the pore size distribution from the particle size distribution, which clearly demonstrated that the value of γ $\gamma $ is similar to the samples with specific sand content. The values of γ $\gamma $ for soils with various sand contents are summarized in Table 1.…”
Section: Theoretical Descriptionsmentioning
confidence: 99%
“…Therefore, for the similar textures, the γ $\gamma $ can be assumed constant. According to the sand fraction of the samples, Chang and Cheng (2018) provided a reference for determining the γ $\gamma $ values, which could be served as input parameters to predict the pore size distribution from the particle size distribution, which clearly demonstrated that the value of γ $\gamma $ is similar to the samples with specific sand content. The values of γ $\gamma $ for soils with various sand contents are summarized in Table 1.…”
Section: Theoretical Descriptionsmentioning
confidence: 99%
“…The corresponding pore diameters (di) at the ith fraction is converted from the water matric suction using the Jurin's law, which is simplified in the equation of [29]:…”
Section: Pore Size Distribution (Psd)mentioning
confidence: 99%
“…There are numerous approaches in the literature to model soil water retention behavior. A common approach is the conversion of a grain size distribution (GSD) to a pore size distribution (PSD), with each pore in the PSD associated with a volume of water it contains and a suction at which it will drain [11][12][13][14][15][16][17]. This information allows a water retention curve to be built.…”
Section: Key Phenomena For Water Retention Curve Modelsmentioning
confidence: 99%
“…The contact angle of a mineral soil grain is an important factor affecting the predicted suctions of GSD-WRC models, as it determines the drainage suction of a pore from the capillarity law. However, because most soil minerals are hydrophilic with relatively low contact angle values (for example, as low as 17 • for quartz [35,36]), many GSD-WRC models assume a contact angle of zero and achieve good predictions for many soils [11][12][13][14][15][16][17]. In contrast, the materials of interest in this study include coal tailings that have significant coal content, and coal is known to be hydrophobic [37][38][39][40][41][42], which means that a contact angle of 0 • cannot be used nor justified.…”
Section: Contact Angle Between Water and Soil Surfacementioning
confidence: 99%